Stepwise Endoscopy Based on Sigmoidoscopy in Evaluating Pediatric Graft-versus-Host Disease - Lee, Kyung Jae (Pediatr Gastroenterol Hepatol Nutr, 2016)
PURPOSE: The aim of our study was to establish a safe and convenient diagnostic method for acute gastrointestinal (GI) graft-versus-host disease (GVHD) in children by determining the sensitivity and negative predictive values of upper and lower endoscopic biopsies for children suspected of GI GVHD. METHODS: Patients suspected of GI GVHD who received endoscopic evaluation within 100 days after stem cell transplantation and endoscopies between January 2012 and March 2014 in Seoul National University Children's Hospital were included in our study. RESULTS: Fifteen patients with a total of 20 endoscopic procedures were included in our study. Sensitivity at the esophagus, stomach, and duodenum were 22.2%, 30.0%, and 80.0%, respectively. Negative predictive values at the esophagus, stomach, and duodenum were 22.2%, 30.0%, and 60.0%, respectively. Overall sensitivity and negative predictive values of upper endoscopic biopsy for GVHD were 77.8% and 50.0%, respectively. Overall sensitivity and negative predictive values of lower endoscopic biopsy for GVHD were 88.9% and 66.7%, respectively. CONCLUSION: We recommend flexible sigmoidoscopy as a safe and accurate diagnostic tool for GVHD, similar to other studies reported previously. However, if there is no evidence of GVHD on sigmoidoscopy with high index of suspicion of GI bleeding, full colonoscopy and upper endoscopy should be considered.